Logging Response Mechanism and Content Evaluation of Laumontite-Bearing Glutenite Reservoir: A Case Study of Lower Urho Formation of Permian of the Junggar Basin - Jia Jun; Xue Kunlin; Ni Liping; Luo Yang; Liu Yuchao (Geofluids)
The Urho Formation in the Lower Permian System at the Junggar Basin in China commonly develops zeolite cements. The presence of zeolite minerals in various states of occurrence and uneven distribution in glutenite reservoirs makes it indeterminate to interpret the well logging response characteristics such as acoustic, resistivity, radioactivity, and nuclear magnetic resonance (NMR). This poses significant challenges for the evaluation of well loggings in glutenite reservoirs containing laumontite and the determination of oil and gas reserves. In this study, through petrophysics experiments such as whole-rock X-ray diffraction, conventional petrophysical properties, mercury injection, and electron microprobe analysis, the characteristics of glutenite reservoirs containing laumontite and the well logging response mechanisms were analyzed from the perspectives of mineral composition of rocks, geochemical characteristics, and principle of loggings. A multimineral optimization method was used to calculate the laumontite content. The results indicate that in the study area, the cementation of zeolite minerals dominated by laumontite suppresses the pore development in the reservoir, which is a crucial factor in the formation of complex pore structures and low-porosity low-permeability reservoirs. Since laumontite exhibits a water-bearing framework structure with numerous micropores and crystal water, the laumontite-bearing glutenite reservoirs are characterized by low natural gamma radiation, low density, high neutron porosity, and high electrical resistivity. The acoustic interval transit time shows no significant differences, while the NMR T2 spectrum exhibits a short relaxation time.